FACTIBILIDAD TÉCNICA-AMBIENTAL, FINANCIERA Y ECONÓMICA DE PLASTICERAMIK - EMPRESA PRODUCTORA Y COMERCIALIZADORA DE BALDOSAS A BASE DE PLÁSTICO RECICLADO EN LOJA - Mera Romero, Cinthya Elizabeth (2019)
This research work entitled "TECHNICAL-ENVIRONMENTAL, FINANCIAL AND ECONOMIC FEASIBILITY OF PLASTICERAMIK - PRODUCTION AND COMMERCIALIZING COMPANY OF TILES BASED ON PLASTIC RECYCLED IN LOJA" was carried out in the city of Loja, with the following general objective: Conduct a feasibility study for the creation of a Production and Commercialization Company of tiles based on 100% recycled plastic, in the city of Loja, in order to make known whether the project is feasible or not. For this, methods such as the inductive and the deductive were used, techniques such as the survey for the plaintiffs were also used, which allowed the collection of relevant information for this project. Thus, being able to carry out the market study in which the surveys were applied to people requesting construction permits in the city of Loja, being able to determine that there is a demand of 31,141.74 m2; As for the offer, it is 1648.48 m2, and with this an unsatisfied demand of 29,493.26 m2 is obtained. In the technical study we proceeded to determine the location of the company, which will be located in the city of Loja; Barrio el Valle belonging to the parish El Valle proper in the industrial sector; Also the distribution of the plant and the technical requirements to maximize their capacity, making an orderly and systematic arrangement of the entire production area, it was analyzed that the installed capacity is 93,440 m2 per year, on the other hand, the capacity used it is 16,640 m2; The company generates 7 jobs during its life cycle in the market; In addition the flowcharts of processes and times, as well as the balance of materials, apart from that there is an environmental study by a specialized person, which indicates the benefits of the company in the market. 5 In the administrative study, the constitution of the company was determined, the same one that will have as its corporate name a single person printed, likewise, the organizational charts and function manuals of each personnel were prepared which are necessary for the operation of the company. In the financial study, the total investment was determined, which amounts to US $ 107,092.94, this investment is financed by the personal contribution and a bank loan. In the financial evaluation came to check the feasibility of the project submitted to obtain favorable results in indicators such as: the NPV that results in $ 106.638,10 US dollars, the IRR is 39.46%, the CBR is $ 0.29 cents dollar and the period of capital recovery that is 3 years, 9 months and 25 days. The sensitivity analysis shows that the project can withstand changes in the market during the project years.